COMPARATIVE ANALYSIS OF QUALITY OF SERVICE PERFORMANCE OF VIDEO STREAMING SERVICES USING OSPF AND EIGRP NETWORKS - Fransiskus Simson; Indrastanti R Widiasari (JIKO (Jurnal Informatika dan Komputer), 2023)
In the era of globalization, computer networks are developing very rapidly and complex human needs make it possible to exchange information and communicate over long distances. In order for video streaming service providers from servers to be accessed by service users, it requires a process of sending data packets through a path called routing. OSPF is a routing protocol that applies network speed based on metrics to consider paths to other networks. EIGRP is a routing protocol that applies bandwidth and delay-based formulas to calculate metrics to determine routes. EIGRP is a type of Dynamic routing protocol. Throughput on OSPF and EIGRP differs depending on video quality. Jitter values on OSPF and EIGRP vary depending on the quality of the video used. There is a difference in the delay time experienced for each video quality when using OSPF and EIGRP. At all video quality levels, no packets are lost using either OSPF or EIGRP routing. OSPF and EIGRP performance is sufficient in sending video data. Throughput parameters, EIGRP has better performance than OSPF for all video qualities. However, for the jitter parameter, OSPF has better performance than EIGRP at 360p and 480p video quality. While on the delay parameter, both protocols have the same good performance. In the packet loss parameter, both protocols have the same performance without packet loss.